TEKNIK PEMBUATAN PERNIS DARI DAMAR UNTUK USAHA KECIL - E Edriana; Erik Dahlian; E Suwardi Sumadiwangsa (Jurnal Penelitian Hasil Hutan, 2004)
This study  was intended to identify an appropriate formula  ill  manufacturing varnish for  a small-scale industry.  Resin used in the formula consisted of two types,  namely "The ash" and "the low grade".  Other ingredients were technical - grade toluene, mixed with other agents (synthetic alkyd, kerosene, dry cobalt, and dry calcium) at several compositions.  Results revealed  that ash resin could be used for  producing good quality varnish suitable for  small scale industry using certain formula. Resin was dissolved in  toluene at 65% and added with 25% synthetic alkyd. 8.8% kerosene, 0.3% dry cobalt, and 0.9% dry calcium.  The varnish took 3 hours to dry, with glossy appearances and convenient contact senses.  Varnish made from  low-quality resin exhibited transparent appearances, but thickened after 24 hours exposure as affected by air contamination. The resulting varnish had a lowerproduction costs than those of the commercial ones.